Exploring the pharmacological action mechanism of Ligusticum Chuanxiong-Piper Longum couplet medicines on the treatment of migraine based on network pharmacology - Ti Li; Shupeng Guo; Meixi Lu; Fang Lu; Tianjiao Lu; Chunze Zheng (Frontiers Media S.A., 2022)
Objective: To study the mechanisms of the Ligusticum chuanxiong Hort.-Piper longum L. herbal pair (LPHP) in the treatment of migraine using network pharmacology.Methods: The active constituents of LPHP and their targets were searched for and screened using the Chinese Medicine System Pharmacology Database. Genes related to migraine were searched on GeneCards, Online Mendelian Inheritance in Man and other databases. Cytoscape was used to construct and combine active component-target and disease-target networks. The core target was screened by network topology analysis, and the Metascape database was used for gene ontology analysis of key targets and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis to explore the molecular mechanisms in the treatment of migraine.Results: A total of 28 active constituents of LPHP were obtained through database screening and literature review, and 60 cross-linking targets were obtained. The target sites were analysed using a protein-protein interaction network to obtain six target proteins with a greater degree of relevance. These were identified as the main targets for the treatment of hypertension, and these key targets were found to be associated with 20 signalling pathways, including neuroactive ligand-receptor interaction, the calcium signalling pathway, the cGMP-PKG signalling pathway, pathways in cancer and the cyclic adenosine 3',5'-cyclic monophosphate (cAMP) signalling pathway.Conclusion: This study reveals the molecular mechanism of LPHP in the treatment of migraine from the perspective of network pharmacology and provides a basis for further research and molecular mechanism research.